2018
DOI: 10.1021/acs.joc.8b01588
|View full text |Cite
|
Sign up to set email alerts
|

Visible-Light-Activated Catalytic Enantioselective β-Alkylation of α,β-Unsaturated 2-Acyl Imidazoles Using Hantzsch Esters as Radical Reservoirs

Abstract: An efficient and practical method for the enantioselective β-functionalization of α,β-unsaturated 2-acyl imidazoles is described. The method uses a previously devised chiral-at-metal rhodium catalyst (Λ-RhS, 4 mol %) along with Hantzsch ester derivatives as alkyl radical sources. The rhodium complex exerts a dual role as the visible-light-absorbing unit upon substrate binding and as the asymmetric catalyst. The method provides up to quantitative yields with excellent enantioselectivities up to 98% ee and can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(36 citation statements)
references
References 65 publications
0
35
0
Order By: Relevance
“…4-alkyl-1,4-dihydropyridines (2) were prepared according to literature procedure. [5][6][7][8] Compounds 2a -2c, 2d -2i are known, 2e and 2j are new compounds and were prepared following General procedure I. Compound 2h is a known compound and was prepared following General procedure II.…”
Section: S3: Typical Procedures For the Preparation Of Substituted Dhp Estersmentioning
confidence: 99%
See 1 more Smart Citation
“…4-alkyl-1,4-dihydropyridines (2) were prepared according to literature procedure. [5][6][7][8] Compounds 2a -2c, 2d -2i are known, 2e and 2j are new compounds and were prepared following General procedure I. Compound 2h is a known compound and was prepared following General procedure II.…”
Section: S3: Typical Procedures For the Preparation Of Substituted Dhp Estersmentioning
confidence: 99%
“…Pd-catalyzed asymmetric allylic substitution reactions of vinyl epoxides 7 and vinyl cyclic carbonates (VCCs) 8 serving as prochiral electrophilic allylic surrogates have been recently reported as efficient approaches to forge compounds featuring a tetrasubstituted carbon stereocenter. While only a handful of studies report the efficient use of olefin-substituted VCCs in allylic alkylation (Scheme 1b, R 2 -R 4 ≠ H) 9 and more particularly towards branched allylic products, 9h,i as far as we are aware only two reports exist that briefly discuss the use of more elaborate carbonate ring substituted congeners (Scheme 1b, R 5 and R 6 ≠ H).…”
mentioning
confidence: 99%
“…); the omission of the catalyst only provided 7 a in a much lower yield even after prolonging time (Table , entry 2: 20 % yield). To improve the enantioselectivity, a comparison of steric environments between ΛCo1 and Meggers’ catalyst ΛRh1 (Figure , M=Rh, X=S) was performed. As shown in Figure , the coordination of a chiral diamine unit with a Co center, though being favored to induce the chirality of the metal center, makes the steric tert ‐butyl groups distant from the plane comprising of Co, Cl, and O atoms (S ΛCo1 =5.05 Å vs. S ΛRh1 =4.57 Å).…”
Section: Figurementioning
confidence: 99%
“…Control experiments showed that both visible light and photocatalyst are necessary (Table , entries 9 and 10), and replacement of the central metal Co with other 3d metals (that is, Mn, Fe, Ni, Cu, and Zn), 4d metals (that is, Ru and Rh) or the 5d metal Ir, only results in lower or even no enantioselectivity (see the Supporting Information for details). Consistent with the control experiments, UV/Vis absorption and cyclic voltammetry studies of ΔCo1 complex and ΔCo1 – 5 a complex indicated that both of these two complexes cannot be a bifunctional catalyst in this transformation (see the Supporting Information for details) …”
Section: Figurementioning
confidence: 99%
“…Very recently, the concept could be extended to the use of Hantzsch esters 56 as alkyl radical reservoirs (Scheme ) . The authors assumed that both mechanisms A and B could operate simultaneously.…”
Section: Metal‐centered Chirality Catalysismentioning
confidence: 99%